2003
DOI: 10.4141/p02-072
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extra-strong gluten on quality parameters in durum wheat

Abstract: Woods, S. M. 2003. The effect of extra-strong gluten on quality parameters in durum wheat. Can. J. Plant Sci. 83: 525-532. Durum wheat (Triticum durum L.) cultivars with extra-strong gluten characteristics have become a unique quality type preferred by several domestic and international pasta processors. Durum genotypes with extra-strong gluten characteristics were compared to conventional gluten strength types to determine the relative levels of gluten strength and the importance of this characteristic in pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
(10 reference statements)
0
17
4
Order By: Relevance
“…A conspicuous r g appeared between wet gluten content and cooking loss, indicating that durum genotypes that had high semolina gluten content showed low pasta cooking loss, as it was observed for protein content (Table II). This result is not consistent with results reported by Ames et al (2003) that CSF had significant correlations with both protein and wet gluten quantity. Semolina wet gluten content showed significant r p (P < 0.05) but nonsignificant r g (P > 0.05) with CSF.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…A conspicuous r g appeared between wet gluten content and cooking loss, indicating that durum genotypes that had high semolina gluten content showed low pasta cooking loss, as it was observed for protein content (Table II). This result is not consistent with results reported by Ames et al (2003) that CSF had significant correlations with both protein and wet gluten quantity. Semolina wet gluten content showed significant r p (P < 0.05) but nonsignificant r g (P > 0.05) with CSF.…”
Section: Resultscontrasting
confidence: 99%
“…For the unextractable fractions, all of the SE-HPLC parameters showed positive and significant r p and r g values with CSF except for UP3 (Table V). Ames et al (2003) also highlighted that low CSF values were shown for durum genotypes with strong gluten characteristics when their protein contents were low. Notably, UF2 and UF3 showed high r g values, indicating that the quantity of unextractable monomeric proteins may be highly associated with CSF for durum genotypes.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…, 1995). Four, 1 cm long, rinsed pasta pieces were subjected to a load weight of 1500 g and held for 30 s (Ames et al. , 2003).…”
Section: Methodsmentioning
confidence: 99%